Lourdes March and Alicia Ríos: El Libro del Aceite y la Aceituna - Davidson, Alan E (Petits Propos Culinaires, 1990)
Lourdes March and Alicia Ríos: El Libro del Aceite y la Aceituna: Alianza, Madrid, 1989: 458 pp, drawings by Lupe Ríos, extensive bibliography, index to recipes, paperback, [price].